PENGEMBANGAN LKS BERBASIS KETERAMPILAN PROSES SAINS PADA MATERI STOIKIOMETRI - Aditya Eka Putra; Noor Fadiawati; Nina Kadaritna (Universitas Lampung, 2015)
This research was using research and development method which purposed to develop the student worksheets based on science process skills on the topic of stoichiometry, and to describe teachers and students responses about the student worksheets as development product. The student worksheets as development product was tested in the 10th grade of SMAN 14 and SMAN 9 Bandar Lampung to indentity the teachers and students responses. From the results of the teachers responses towards students worksheets which were developed, namely students worksheets based on science process skills on the stoichiometry of chemistry, it were obtained the percentage in aspects of the suitability of the contents, the constructions, and the readability were 88,17%; 88%; and 89,04%, respectively. The results of student responses to the readability and attractiveness were 88,52% and 87,07%, respectively. The result showed that the suitability of contents, the constructions, the readibility, the attractiveness aspects were classified very high category. Based on it, the students worksheets was declared feasible to be used.Penelitian ini menggunakan metode penelitian dan pengembangan yang bertujuan untuk mengembangkan LKS berbasis keterampilan proses sains pada materi stoikiometri, dan untuk mendriskripsikan respon guru dan siswa tentang lembar kerja siswa sebagai produk pengembangan. Lembar kerja siswa sebagai produk pengembangan diujikan di kelas X pada SMAN 14 dan SMAN 9 Bandar Lampung untuk mengidentifikasi respon guru dan siswa. Dari hasil tanggapan guru terhadap LKS yang dikembangkan yaitu LKS berbasis keterampilan proses sains pada materi stoikiometri, diperoleh persentase pada aspek kesesuaian isi, keterbacaan, dan kemenarikan sebesar 88,17%; 88%; dan 89,04%. Hasil tanggapan siswa terhadap keterbacaan dan kemenarikan sebesar 88,52% dan 87,07%. Dapat disimpulkan bahwa aspek kesesuaian isi, konstruksi, keterbacaan, dan kemenarikan yang semuanya dikategorikan sangat tinggi. Berdasarkan keterangan di atas, diperoleh bahwa LKS sudah dapat digunakan.Kata kunci: stoikiometri, keterampilan proses sains, LKS